Culturally modified cognitive processing therapy for Karen refugees with posttraumatic stress disorder: A pilot study. (13th June 2019) - Bernardi, Jessica; Dahiya, Mini; Jobson, Laura
Abstract: Karen refugees, many originating from Myanmar, have suffered one of the longest civil wars in history and have thus witnessed and experienced substantial trauma. Refugees from Myanmar are currently one of the largest refugee groups being resettled in Western countries. This study investigated the feasibility and acceptability of a modified cognitive processing therapy (CPT) group program for Karen refugees with posttraumatic stress disorder (PTSD; N =7). It was found that the CPT program was well accepted, with high satisfaction and no drop‐outs. At posttreatment all participants no longer met PTSD diagnostic criteria and had a reliable improvement in PTSD symptoms when compared with pretreatment scores. At 3‐month follow‐up four participants (57% of sample) did not meet PTSD diagnostic criteria and three participants (43%) had a reliable improvement in PTSD symptoms when compared with pretreatment scores. However, at follow‐up four participants (57% of the sample) had a reliable worsening in PTSD symptoms when compared with their posttreatment PTSD symptom levels. Although the study found that the modified CPT was acceptable and feasible, future research is needed to develop and enhance strategies to ensure that refugees benefit from empirically supported treatments.